2020
DOI: 10.1136/bmjopen-2020-037419
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology and prognostic risk factors of mortality in patients with pneumonia receiving glucocorticoids alone or glucocorticoids and other immunosuppressants: a retrospective cohort study

Abstract: ObjectivesLong-term use of high-dose glucocorticoids can lead to severe immunosuppression and increased risk of treatment-resistant pneumonia and mortality. We investigated the aetiology and prognostic risk factors of mortality in hospitalised patients who developed pneumonia while receiving glucocorticoid therapy alone or glucocorticoid and other immunosuppressant therapies.DesignRetrospective cohort study.SettingSix secondary and tertiary academic hospitals in China.ParticipantsPatients receiving glucocortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 41 publications
0
13
1
Order By: Relevance
“…CMV interstitial pneumonitis reports the highest frequency in hematopoietic stem cell transplant (HSCT) recipients and in solid organ transplant recipients, where it is associated with an increase in terms of mortality [ 36 ]. A study investigating the complications of patients undergoing bone marrow transplantation identified 16 cases of CMV pneumonia.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…CMV interstitial pneumonitis reports the highest frequency in hematopoietic stem cell transplant (HSCT) recipients and in solid organ transplant recipients, where it is associated with an increase in terms of mortality [ 36 ]. A study investigating the complications of patients undergoing bone marrow transplantation identified 16 cases of CMV pneumonia.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…CMV interstitial pneumonitis reports the highest frequency in hematopoietic stem cell transplant (HSCT) recipients and in solid organ transplant recipients, where it is associated with an increase in terms of mortality [36].…”
Section: Cytomegalovirusmentioning
confidence: 99%
“…Although the dose of dexamethasone used in the RECOVERY trial (6 mg daily for up to 10 days) may not act as immunosuppressive, it may contribute to the reactivation of CMV when combined in the presence of factors such as severe lymphopenia or prolonged MV [2,11]. In fact, previous studies have reported that corticosteroid use is associated with increased risk of CMV reactivation [12–14]. The cause of the recurrent respiratory distress requiring reintubation in the present case was probably due to remnant inflammation caused by COVID‐19 pneumonia.…”
Section: Discussionmentioning
confidence: 77%
“…In mouse models, intratracheal infection of neutropenic mice with AB led to the development of severe acute lung injury and increased mortality when compared to control mice (Joly-Guillou et al, 1997). Consistent with this finding, multiple studies have demonstrated respiratory failure, neutropenic fever, and high rates of mortality in neutropenic patients diagnosed with AB pneumonia (Nunley et al, 2010;Li et al, 2020). Along with neutrophils, macrophages play a key role in the response to AB infection.…”
Section: Acinetobacter Baumanniimentioning
confidence: 72%